2019
DOI: 10.1038/s41598-018-38443-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential PI(4,5)P2 sensitivities of TRPC4, C5 homomeric and TRPC1/4, C1/5 heteromeric channels

Abstract: Transient receptor potential canonical (TRPC) 4 and TRPC5 channels are modulated by the Gαq-PLC pathway. Since phosphatidylinositol 4,5-bisphosphate (PI(4,5)P2) maintains TRPC4 and TRPC5 channel function, the Gαq-PLC pathway inhibits channel activity by depleting PI(4,5)P2. Here we investigated the difference in PI(4,5)P2 sensitivity between homomeric and heteromeric TRPC channels. First, by using a Danio rerio voltage-sensing phosphatase (DrVSP), we show that PI(4,5)P2 dephosphorylation robustly inhibits TRPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…PLC modulation on TRPCs is inseparable with PI(4,5)P 2 , the substrate of PLC. TRPC1/4 and TRPC1/5 channels interact with the PH domain of PLCδ through PI(4,5)P 2 [32]. PI(4,5)P 2 was shown to be essential for TRPC4 activation [3].…”
Section: Discussionmentioning
confidence: 99%
“…PLC modulation on TRPCs is inseparable with PI(4,5)P 2 , the substrate of PLC. TRPC1/4 and TRPC1/5 channels interact with the PH domain of PLCδ through PI(4,5)P 2 [32]. PI(4,5)P 2 was shown to be essential for TRPC4 activation [3].…”
Section: Discussionmentioning
confidence: 99%
“…A different study was reported which shares the similar context that PIP 2 is necessary to maintain the opening of TRPC4β [37]. In this study a voltage-sensitive phosphatase (VSP) system was employed.…”
Section: Phosphatidylinositol 45-bisphosphate (Pip 2 )mentioning
confidence: 99%
“…However, most of all, it was rapid and prominent desensitization of the channels that made dissecting downstream components out of overall effect of the Gq pathway to TRPC channels challenging. With an astonishing consistency, TRPC4 or 5 channels showed prominent desensitization right after strong activation whenever the channels were activated by Gq-protein coupled receptors (GqPCR, e.g., mAChR1, or 3, histamine receptor subtype 1) [19,21,22,[37][38][39][40][41][42][43]59,71,72]. As an alternative, a non-specific G-protein activator such as [GTPγS] i has been used [35,45,46].…”
Section: General Aspect Of G-protein Mediated Gating Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…However, which mechanism makes this difference is still obscure. Many researches demonstrated the effect of downstream molecules on TRPC channels, which includes PLC, phosphatidylinositol 4,5-biphosphate (PIP2) [1][2][3][4] , diacylglycerol (DAG) 5,6 , protein kinase C (PKC) 7 and Ca 2+ . We previously emphasized the self-limiting mechanism of Gαq pathway on channels that Gαq protein solely activates TRPC1/4 and TRPC1/5 channels, and then PIP2 depletion and PKC or Ca 2+ inhibits them 8,9 .…”
Section: Introductionmentioning
confidence: 99%